Global, regional, and national burdens of low back pain in women of childbearing age from 1990 to 2021: an analysis based on the global burden of disease study 2021 - Shiwen Zhang; Xuan Ma; Yao Yao; Huashan Pan; Lijuan Zou (BMC Public Health)
Abstract Background Low back pain (LBP) is very common in women of child bearing age (WCBA) and is a major burden on individuals and society, but studies about it have not been reported. Methods Trend analyses were based on data from the Global Burden of Disease, Injuries, and Risk Factors Study (GBD) 2021. We investigated global trends in the number of prevalence cases, prevalence and the years lived with disability (YLDs), and the YLDs rate for LBP in the WCBA. We used joint point regression analyses to report average annual changes and identify the most variable years in the global trend. Simultaneously, we further analyzed these trends by stratifying them by the region, nation, and age. Results Globally, the number of the prevalence and the YLDs for LBP increased substantially from 1990 to 2021(the prevalence: 39.65%) (the YLDs: 39.53%), whereas the prevalence and the YLDs rate of WCBA LBP decreased (the prevalence: AAPC: -0.1355 [95% CI -0.1419 to -0.1288) (the YLDs: AAPC: -0.1365 [95% CI -0.1427 to -0.1302]). Regionally, the prevalence and the YLDs rate of LBP among WCBA in the medium socio-demographic index region showed an increasing trend(the prevalence: AAPC: 0.1291 [95% CI: 0.118 to 0.1396]) (the YLDs: AAPC: 0.1371 [95% CI: 0.1251 to 0.1499]). Nationally, Thailand and Vietnam were the countries with the largest increases in YLD rates(Thailand: AAPC: 0.7742 [95% CI: 0.7589 to 0.7904]) (Vietnam: AAPC: 0.7364 [95% CI: 0.7263 to 0.7468]). In age patterns, the highest prevalence and YLDs rates of LBP were found among women in the 45–49 age group(the prevalence: 14,412.77 per 100,000 in 2021 [95% UI: 10,482.27 to 19,077.3]) (the YLDs: 1,639.56 per 100,000 population (95% UI: 1,035.24 to 2,494.9]). Conclusion Despite declines in the prevalence and YLDs of WCBA LBP, the burden remains high. Age- and region-specific prevention and healthcare strategies should be optimized to meet the needs of WCBA and reduce the burden of disease.